Design a remote sensing of multi-BOTDR fiber optic sensors for fuel pipeline monitoring - Arafat A. A. Shabaneh; Raed S.M. Daraghma (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
The necessity for environmental protection has led to the development of diﬀerent sensors for monitoring fuel pipelines to avoid explosion, leakage, and corrosion. Distributed optical ﬁber sensors-based Brillouin scattering have become progressively common because of their novel feature of simultaneously determining temperature, vibration, and strain. The stimulated Brillouin scattering (SBS) threshold power, sensing distance, single-mode fiber cable length, and sensing accuracy are serious parameters to the implementation of Brillouin optical time-domain reﬂectometry (BOTDR) sensor. In this study, remote sensing of multi-BOTDR fiber optic sensors for fuel pipeline monitoring is designed and presented. The results of simulations and theoretical explainations on suppressing ﬁber optic nonlinearity are analyzed. Results show that an SBS suppression via 16 dB is required to attain the maximum multi-remote sensing distance of up to 20 km for each network and a perfect frequency shift of 11 GHz. An open eye pattern corresponds to minimal signal distortion with a high Q-factor of 22 for the developed sensor. The highest sensing accuracy of 0.3318 %/K indicating power change (%) is observed from 290–300 K at 193.1 THz operating frequency.